2008
DOI: 10.1016/j.vetimm.2008.01.015
|View full text |Cite
|
Sign up to set email alerts
|

In vivo CXCR4 expression, lymphoid cell phenotype, and feline immunodeficiency virus infection

Abstract: Primary isolates of feline immunodeficiency virus (FIV) appear to require binding to CD134 in conjunction with CXCR4(X4) to infect IL-2 dependent T-cell derived cells in culture. However, much less is known about the role of X4 for infection of cells in vivo. To investigate the correlation between X4 expression and FIV infection in cats acutely infected with FIV-C-Pgmr we used high speed fluorescence activated cell sorting and realtime PCR to co-analyze cell phenotypes from lymph node, thymus, bone marrow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
1
5
0
2
Order By: Relevance
“…FIV Env domains responsible for binding of CXCR4 and CD134 have also been mapped and found to be independent of each other, as expected [36,53]. Additionally, CXCR4 expression has been detected in lymph node, thymic and bone marrow-derived CD4+, CD8+ T lymphocytes, CD21+ B lymphocytes and unfractionated CD4-/CD8-/CD21-cells [54]. Results from this report also revealed FIV infection in both CXCR4+ and CXCR4-cell populations, as determined by quantitative polymerase chain reaction (qPCR) assay of isolated cell populations for FIV proviral DNA.…”
Section: Fiv Receptor Usagesupporting
confidence: 60%
See 1 more Smart Citation
“…FIV Env domains responsible for binding of CXCR4 and CD134 have also been mapped and found to be independent of each other, as expected [36,53]. Additionally, CXCR4 expression has been detected in lymph node, thymic and bone marrow-derived CD4+, CD8+ T lymphocytes, CD21+ B lymphocytes and unfractionated CD4-/CD8-/CD21-cells [54]. Results from this report also revealed FIV infection in both CXCR4+ and CXCR4-cell populations, as determined by quantitative polymerase chain reaction (qPCR) assay of isolated cell populations for FIV proviral DNA.…”
Section: Fiv Receptor Usagesupporting
confidence: 60%
“…Table 1 summarizes key studies that have identified FIV cell reservoirs and the modalities used to detect infection or susceptibility to infection. It is important to note that the leukocyte subsets that have proven most consistently infected in vivo and susceptible to infection in vitro are CD4+ T cells and monocyte/ macrophages, which are also target cell reservoirs for HIV [13,49,54,[60][61][62]. Evidence thus far is conflicting regarding productive infection of dendritic cells in vivo [29,30,54,63], although multiple studies support productive FIV infection of cultivated dendritic cells [43,63,64].…”
Section: Cell Reservoirs Of Fivmentioning
confidence: 99%
“…Infection with the feline immunodeficiency virus predisposes cats to opportunistic infections (Pedersen et al 1987, O`Neil et al 1995, Paillot et al 2005, Troth et al 2008, Tompkins & Tompkins 2008. However, none of the animals included had severe clinical signs, suggesting that the hygienic conditions of the shelter and the care provided to the animals were appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…A alteração clínica mais evidente foi a linfadenomegalia que, de início era discreta e limitada aos linfonodos da região cervical, ao fim da décima segunda semana envolvia os outros linfonodos periféricos e também os abdominais. A hepatoesplenomegalia reflete o comprometimento do tecido monocítico-macrofágico (Brown et al 1991), como ocorre em outras infecções em que linfócitos e monócitos/macrófagos são envolvidos (Troth et al 2008). Segundo Callanan et al (1993), a linfoadenopatia observada na fase aguda da infecção pelo FIV é caracterizada ao exame histopatológico por hiperplasia folicular, seguida de resposta humoral representada pelo surgimento de plasmócitos nos folículos linfoides e no parên-quima extrafolicular e ativação do centro germinativo.…”
Section: Discussionunclassified
“…O FIV infecta linfócitos T CD4, T CD8, linfócitos B e macrófagos (Dean et al 1996, Troth et al 2008, o que resulta na perda lenta e progressiva de linfócitos T CD4, inversão da relação CD4/CD8 e o bloqueio da atividade mitótica linfocitária após estimulação antigênica (Torten et al 1991). Além do aumento na predisposição a várias doenças infecciosas, a imunossupressão resultante da infecção pelo FIV leva a uma maior predisposição ao desenvolvimento de tumores linfoides (Willis 2000).…”
Section: Introductionunclassified